Peran RPTRA Dalam Meningkatkan Kemampuan Memahami Kosakata Bahasa Inggris (Melalui Media Flash Card) pada Anak-Anak Usia 7 – 12 Tahun - Nurul Badriyatul Muthoharoh; Nani Mulyani (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Abstract: The purpose of learning English at 7-12 years or the basic school level to develop the ability of leraners to learn and improve things in their lives. The ability to understand English vocabularies are very important foundation that must be mastered in learning English, many vocabularies are controlled. It will be more sophisticated using their English. In studying English language vocabulary in children 7-12 years found a lot of basic, appropriate in the price of new vocabulary. Therefore, the author with the teachers in RPTRA Lenteng agung interested in conducting research by using Flash Card media in effort to improve the understanding of vocabulary. This study aims to determine the role of RPTRA Lenteng Agung in improving the ability of learners in English lessons by using flashcard media in RPTRA Lenteng Agung. The research method used is action research with the following stages: planning, implementation of action, observation and reflection. Data processing techniques used in this study are: (1) test, (2) interview, (3). The results of research in the implementation of the first act of learning has not achieved maximum results, this can be done by using media that is done by using flashcard media and there are still learners who feel confused with what instructed tutor that gives the average value obtained by learners in cycle I is 68, with mastery learn about 70%. While in cycle II, the increase with the average average obtained by learners in cycle II is 86, with learning mastery about 100%. Keywords: RPTRA, Flashcard, English Vocabularies